Saccharomyces boulardii: What Makes It Tick as Successful Probiotic? - Pedro Pais (Journal of Fungi, 2020)
Saccharomyces boulardii is a probiotic yeast often used for the treatment of GI tract disorders such as diarrhea symptoms. It is genetically close to the model yeast Saccharomyces cerevisiae and its classification as a distinct species or a S. cerevisiae variant has long been discussed. Here, we review the main genetic divergencies between S. boulardii and S. cerevisiae as a strategy to uncover the ability to adapt to the host physiological conditions by the probiotic. S. boulardii does possess discernible phenotypic traits and physiological properties that underlie its success as probiotic, such as optimal growth temperature, resistance to the gastric environment and viability at low pH. Its probiotic activity has been elucidated as a conjunction of multiple pathways, ranging from improvement of gut barrier function, pathogen competitive exclusion, production of antimicrobial peptides, immune modulation, and trophic effects. This review summarizes the participation of S. boulardii in these mechanisms and the multifactorial nature by which this yeast modulates the host microbiome and intestinal function.